How Self-Disclosure in Online Postings Affects Female Readers' Stigmatisation Towards Mothers with a Disability - Alexander Röhm; Michélle Möhring; Michelle Grengel; Matthias R. Hastall (University of Zurich, IKMZ - Department of Communication and Media Research, 2021)
Self-disclosure of a health problem or a disability in online environments can be helpful to reduce stigmatisation and to empower marginalised individuals. Although stigmatisation leads to adverse health outcomes, it is still unclear which factors reduce readers' stigmatising attitudes. This 2 × 2 × 3 × 2 online-experiment with 715 female participants examined how the depiction of self-disclosure of a mother's disability, her coping with a stressful situation, and the child's type of disability and sex in a fictional blog post affect female readers' stigma-related attitudes. The role of readers' perspective taking is also studied in this regard. A MANOVA yielded two main effects: Disclosure of the mother's disability reduced social distance compared to the control condition (no disability). Female respondents with a high ability for perspective taking reported less stigmatising attitudes than female respondents scoring low in this regard. Both effects are also reflected in a four-way interaction with mother's coping and child's sex. Overall, results indicate a high potential of self-disclosures for anti-stigma communication. Implications for blogging about a disability and future health communication research are discussed.